ASSESSMENT AND FOLLOW-UP PROCESS IN HOUSING FIRST MENTAL HEALTH CASE MANAGEMENT APPROACH - Zadoorian , D. (Արդի հոգեբանություն, 2020)
The application of psychological science in vast majority of interdisciplinary programs becomes all-embracing in the western societies. Nowadays, the word mental health has a broader meaning to it and touches each and every aspect of human life. Consequently, anything that affects our mental well-being can be a subject of general or specific studies to find out the level of its importance and the extent to which it affects the quality of our lives. Most of the government programs provide funding for mental health researches that can improve lives of many members of the society. The following steps of the government can assess how to improve the plans, and in particular, the positive outcome of each program based on the person’s needs. In this descriptive paper, the attempt is to provide some information on needs assessment, planning and follow-up in one of the programs funded by the City of Toronto, which is mainly designed to assist clients with mental health and substance use issues to obtain and maintain housing and get stabilized in their daily life.
Keywords: գնահատում; հոգեկան առողջություն; հիվանդների կառավարում; հսկողություն; բնակարան; անօթեւանություն; հոգեմետ նյութերի օգտագործում